An outlier-robust neuro-fuzzy system for classification and regression - Simiński, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Real life data often suffer from non-informative objects - outliers. These are objects that are not typical in a dataset and can significantly decline the efficacy of fuzzy models. In the paper we analyse neuro-fuzzy systems robust to outliers in classification and regression tasks. We use the fuzzy c-ordered means (FCOM) clustering algorithm for scatter domain partition to identify premises of fuzzy rules. The clustering algorithm elaborates typicality of each object. Data items with low typicalities are removed from further analysis. The paper is accompanied by experiments that show the efficacy of our modified neuro-fuzzy system to identify fuzzy models robust to high ratios of outliers.
Keywords: outliers; neuro-fuzzy systems; clustering; classification; regression